Apophysomyces thailandensis (Mucorales, Mucoromycota), a new species isolated from soil in northern Thailand and its solubilization of non-soluble minerals - Surapong Khuna (2019)
Copyright Surapong Khuna et al. A new species of soil fungi, described herein as Apophysomyces thailandensis, was isolated from soil in Chiang Mai Province, Thailand. Morphologically, this species was distinguished from previously described Apophysomyces species by its narrower trapezoidal sporangiospores. A physiological determination showed that A. thailandensis differs from other Apophysomyces species by its assimilation of D-turanose, D-tagatose, D-fucose, L-fucose, and nitrite. A phylogenetic analysis, performed using combined internal transcribed spacers (ITS), the large subunit (LSU) of ribosomal DNA (rDNA) regions, and a part of the histone 3 (H3) gene, lends support to our the finding that A. thailandensis is distinct from other Apophysomyces species. The genetic distance analysis of the ITS sequence supports A. thailandensis as a new fungal species. A full description, illustrations, phylogenetic tree, and taxonomic key to the new species are provided. Its metal minerals solubilization ability is reported.